6(3-4-x)=3x+6

Simple and best practice solution for 6(3-4-x)=3x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3-4-x)=3x+6 equation:



6(3-4-x)=3x+6
We move all terms to the left:
6(3-4-x)-(3x+6)=0
We add all the numbers together, and all the variables
6(-1x-1)-(3x+6)=0
We multiply parentheses
-6x-(3x+6)-6=0
We get rid of parentheses
-6x-3x-6-6=0
We add all the numbers together, and all the variables
-9x-12=0
We move all terms containing x to the left, all other terms to the right
-9x=12
x=12/-9
x=-1+1/3

See similar equations:

| -4(6x+2)=-24x+8 | | -5/2(4x-6)=10 | | -9=m/2 | | 4=3v-5 | | 3/x-5=-7/x+5 | | 4/3=1/5(2.5x+10/3) | | 9(x-6)+5(x+6)=6x-6 | | 5(7x+4)=4x+6 | | 7(x+17)=17x-6 | | 18x+1+11x+5=180 | | -4.3=3.8-0.09x | | 64=2x-9 | | 7(x+17)=17-6 | | 6a-4=@4 | | 5(x-6)=5x+19 | | -5/8m=1/2 | | -t−5=-8+2t | | 2n+2n-6=8 | | -3p=-4p+6 | | -10c+2c+6=3-8c | | 84=1.5x | | n÷20=2 | | 6x+3(-3+2x)=1-x | | 6/x-8=2/x-6 | | 8p^2-12p+22.5=0 | | 1/2x+1/7=16 | | 6x-3=2-(-6x-2) | | 2x+9x=3x+4 | | 6=r-8 | | 4=2(x=3) | | -z/7=3 | | 1/4x-16=2x-2 |

Equations solver categories